ChemInform Abstract: Highly Diastereoselective Synthesis of Polycyclic Amines via Redox Neutral C—H Functionalization. Issue 10 (February 2016) - Pavan Kumar, Chottanahalli S.; Harsha, Kachigere B.; Sandhya, Nagarakere C.; Ramesha, Ajjalli B.; Mantelingu, Kempegowda; Rangappa, Kanchugarakoppal S.
Abstract: An intramolecular [3+2]‐cycloadditions of in situ generated azomethine ylides is the key step in this synthesis of polycyclic amines.